Aeration performance of triangular-notch weirs - Baylar, A; Bagatur, T; Tuna, A (Chartered Inst Water Environmental Management, 2001)
Hydraulic structures have an impact on the concentration of dissolved oxygen in a river system, even though the water is in contact with the structure for only a short period of time. The same oxygen transfer that would normally occur over several kilometres in a river can occur at a single hydraulic structure, because the flow over a structure is typically highly turbulent, resulting in increased interfacial renewal. Plunging overfall jets from weirs are a good example of this fact, and the aeration properties of such structures have been studied widely in the laboratory and field over a number of years. This technical note (a) describes triangular-notch weirs having a different weir angle a and how they affect aeration performance, and (b) demonstrates that aeration efficiency decreases with increasing weir angle.
Keywords: aeration; aeration efficiency; dissolved oxygen; oxygen transfer; triangular-notch weir